IR alarm system / Wan Nur Amani Wan Nordin, Farhatasya Amran and Siti Hawa Azman - Wan Nordin, Wan Nur Amani; Amran, Farhatasya; Azman, Siti Hawa (2010)
In every period of time, everybody has tried to get facilities for human being. So, now days, security is a great matter that has been discussed between people. There are great number of devices that are used to make your home secure from theft and other kind of crimes. PIR sensor have been used for many years as motion detectors due to their high reliability and resilience to false triggering. They are not adversely affected by airflow like some sensors can be. Also, due to their passive nature, PIR sensors are very low on power consumption and thus suitable for battery powered applications. In this project, we prefer to use PIR detector because this sensor are inexpensive, simple,small than the another type or sensor like ultrasonic detector, microwave detector, glass break detector and Photo-Electric Beams. We also use PIC 16F876A act as a brain of our project Furthermore, this microcontroller are self-reprogrammable under software control. We only build some instruction and load into the PIC.This project is starting to function if the sensor detect the infrared radiation emanating from objects in the field of view. There are 4 mode condition. First, scan input-second pr fourth is detected mode. Once the motion is detected the buzzer would be active and TED will blink more frequency. For the conclusion, alarm system will alert the person in the home from the outsider.